Behavioral and analgesic effect of acepromazine maleate, lidocaine hydrochloride alone or in combination of them in lumbosacral epidural injection in sheep - Najm, Ibrahim M. (The Iraqi Journal of Veterinary Medicine, 2013)
The aim of the present study was to investigate the analgesic effect of Acepromazine 0.05 mg. /kg B. w. and Lidocaine 0.5 mg/kg each alone or in combinations on the flank region in sheep after giving the drugs by lumbosacral injection. Fifteen healthy adult local breed sheep of both sexes weighting (17.50-30 kg) were used. Sheep were divided into three equal groups. Group (A), Acepromazine, group (B) Lidocaine, and group (C) Acepromazine and Lidocaine mixture. Data were collected immediately before administration of drugs (zero time) as control data. Parameters were included clinical measures: Heart Rate, Respiratory Rate, Rectal Temperature, Scores of analgesia of the flank, low abdomen, perineum, tail, hind limbs, fore limb, at time 10, 20, 30, 40, 50, 60, and 70 minutes after administration of drugs. The results revealed significant differences in flank, perineum, tail, low abdomen, and hind limbs analgesia, in which mild analgesia in group (B) at 10 to 50 minutes, and moderate analgesia in it group (C) combination at 10 to 50 minutes but no analgesic effect in group (A). In conclusion indicated that group (C) more effective than group (A) and group (B) alone and there was non-significant difference in rectal body temperature between animal groups, but significant differences in heart rate, respiratory rate